Climate Variability and Dengue Hemorrhagic Fever in Ba Tri District, Ben Tre Province, Vietnam during 2004-2014 - Le Thi Diem Phuong; Tran Thi Tuyet Hanh; Vu Sinh Nam (AIMS Press, 2016)
"Background: Currently, dengue fever/dengue hemorrhagic fever (DF/DHF) is an important public health challenge in many areas, including the Ba Tri District, Ben Tre Province, Vietnam. Methods and Aim: This study was conducted in 2015 using a retrospective secondary data analysis on monthly data of DF/DHF cases and climate conditions from 2004-2014 in Ba Tri District, which aimed to explore the relationship between DF/DHF and climate variables. Results: During the period of 2004-2014, there were 5728 reported DF/DHF cases and five deaths. The disease occurred year round, with peaked from May to October and the highest number of cases occurred in June and July. There were strong correlations between monthly DF/DHF cases within that period with average rainfall (r = 0.70), humidity (r = 0.59), mosquito density (r = 0.82), and Breteau index (r = 0.81). A moderate association was observed between the monthly average number of DF/DHF cases and the average temperature (r = 0.37). The monthly DF/DHF cases were also moderately correlated with the Aedes mosquito density. Conclusions and Recommendations: Local health authorities need to monitor DF/DHF cases at the beginning of epidemic period, starting from April and to apply timely disease prevention measures to avoid the spreading of the disease in the following months. More vector control efforts should be implemented in March and April, just before the rainy season, which can help to reduce the vectordensity and the epidemic risk. A larger scale study using national data and for a longer period of time should be undertaken to thoroughly describe the correlation between climate variability and DF/DHF cases as well as for modeling and building projection model for the disease in the coming years. This can play an important role for active prevention of DF/DHF in Vietnam under the impacts of climate change and weather variability."